Misrouting of glucagon and stathmin-2 towards lysosomal system of α-cells in glucagon hypersecretion of diabetes. Issue 1 (31st December 2022) - Asadi, Farzad; Dhanvantari, Savita
ABSTRACT: Glucagon hypersecretion from the pancreatic α-cell is a characteristic sign of diabetes, which exacerbates fasting hyperglycemia. Thus, targeting glucagon secretion from α-cells may be a promising approach for combating hyperglucagonemia. We have recently identified stathmin-2 as an α-cell protein that regulates glucagon secretion by directing glucagon toward the endolysosomal system in αTC1-6 cells. We hypothesized that disruption of Stmn2-mediated trafficking of glucagon to the endolysosomes in diabetes contributes to hyperglucagonemia. In isolated islets from male mice treated with streptozotocin (STZ), glucagon secretion and cellular content were augmented, but cellular Stmn2 levels were reduced ( p < .01), as measured by both ELISA and immunofluorescence intensity. Using confocal immunofluorescence microscopy, the colocalization of glucagon and Stmn2 in Lamp2A + lysosomes was dramatically reduced ( p < .001) in islets from diabetic mice, and the colocalization of Stmn2, but not glucagon, with the late endosome marker, Rab7, significantly ( p < .01) increased. Further studies were conducted in αTC1-6 cells cultured in media containing high glucose (16.7 mM) for 2 weeks to mimic glucagon hypersecretion of diabetes. Surprisingly, treatment of αTC1-6 cells with the lysosomal inhibitor bafilomycin A1 reduced K + -induced glucagon secretion, suggesting that high glucose may induce glucagon secretion from another lysosomal compartment. Both glucagon and Stmn2 co-localized with Lamp1, which marks secretory lysosomes, in cells cultured in high glucose. We propose that, in addition to enhanced trafficking and secretion through the regulated secretory pathway, the hyperglucagonemia of diabetes may also be due to re-routing of glucagon from the degradative Lamp2A + lysosome toward the secretory Lamp1 + lysosome.